Arabidopsis TWISTED DWARF1 Functionally Interacts with Auxin Exporter ABCB1 on the Root Plasma Membrane([C])([W]) - Wang, Bangjun (American Society of Plant Biologists, 2013)
Plant architecture is influenced by the polar, cell-to-cell transport of auxin that is primarily provided and regulated by plasma membrane efflux catalysts of the PIN-FORMED and B family of ABC transporter (ABCB) classes. The latter were shown to require the functionality of the FK506 binding protein42 TWISTED DWARF1 (TWD1), although underlying mechanisms are unclear. By genetic manipulation of TWD1 expression, we show here that TWD1 affects shootward root auxin reflux and, thus, downstream developmental traits, such as epidermal twisting and gravitropism of the root. Using immunological assays, we demonstrate a predominant lateral, mainly outward-facing, plasma membrane location for TWD1 in the root epidermis characterized by the lateral marker ABC transporter G36/PLEIOTROPIC DRUG-RESISTANCE8/PENETRATION3. At these epidermal plasma membrane domains, TWD1 colocalizes with nonpolar ABCB1. In planta bioluminescence resonance energy transfer analysis was used to verify specific ABC transporter B1 (ABCB1)–TWD1 interaction. Our data support a model in which TWD1 promotes lateral ABCB-mediated auxin efflux via protein–protein interaction at the plasma membrane, minimizing reflux from the root apoplast into the cytoplasm.